Agriculture As the Creator and Guardian Of The Rural Cultural Landscape - Kamila MUSIAL (Communications of International Proceedings, 2023)
Cultural rural landscape in Poland is a subject to further civilizational changes, and this mutual penetration of natural and anthropogenic elements illustrates the relationship between the man and the nature. However recently the idea of sustaining such landscape in good condition has gained ground in science, policy and land use practice. It is ilustrated by different legal acts referring to landscape and nature conservation, due to which there have been also introduced the changes in the legislation. Paper presents various categories of assessing rural landscape, and the spectrum of agricultural landscape spatial value. The cultural landscape can also be treated as a kind of common good, assessed in political, legal and social terms. There were analysed especially that elements, which are realted to plant and animal production, with the actual or potential value of an economic nature, but also concerning ecosystem services.
Keywords: cultural landscape; public goods; ecosystem services; animal production